PROGRAM PELATIHAN PENGEMBANGAN KOMPETENSI GURU SEKOLAH INKLUSI DI SDN KARAWACI 3 TANGERANG - Yunita, Intan; Jessica, Madeline; Utami, Sylvia Dwi; handayani, penny (Jurnal Bakti Masyarakat Indonesia, 2023)
SDN 3 Karawaci Tangerang is one of the schools designated as an inclusive school. Based on the results of theneeds analysis conducted using observation, study of school documents, interviews, and FGDs with teachers,principals, education personnel, students, and parents, it was found that one of the main challenges at SDNKarawaci 3 is the unpreparedness in accommodating the needs of students with disabilities in inclusive schools. Thismain problem is caused by dif iculties in identifying students with disabilities in the classroom, teachers' lack ofcompetence in teaching students with disabilities, inadequate facilities to accommodate students with disabilities,inef ective communication within the school ecosystem and a lack of discipline consistently applied by the school..The training program provided aims to improve teachers' competence in teaching in inclusive schools, with thetheme "Introduction to Characteristics, How to Communicate, and Learning Programs for Students with SpecialNeeds".. The implementation of this training consists of three main sessions, namely Session I discusses thecharacteristics of students with disabilities in inclusive schools, Session II discusses ef ective communicationstrategies between teachers and the school ecosystem, and Session III discusses how to prepare an IndividualLearning Program (IEP). The training evaluation was reviewed from two aspects, namely evaluation of trainingactivities and evaluation of the achievement of objectives. In evaluating the achievement of objectives, the facilitatorteam looked at the achievement of objectives for each session based on participants' responses during discussionsand the pre-test and post-test results. As a result, some participants experienced an increase in the average score onthe post-test in each session, although the results were not significant. ABSTRAK: SDN 3 Karawaci Tangerang adalah salah satu sekolah dasar yang mendapatkan penunjukan sebagai sekolah inklusi.Berdasarkan hasil needs analisis yang dilakukan dengan metode observasi studi dokumen sekolah, wawancara, danFGD kepada guru, kepala sekolah, tenaga kependidikan, siswa dan orangtua siswa, ditemukan bahwa salah satutantangan utama di SDN Karawaci 3 ialah ketidaksiapan dalam mengakomodasi kebutuhan peserta didikberkebutuhan khusus (PDBK) di sekolah inklusi. Masalah utama ini disebabkan oleh kesulitan identifikasi PDBK didalam kelas, kurangnya kompetensi guru dalam mengajar PDBK, fasilitas yang kurang memadai untukmengakomodasi PDBK, komunikasi yang tidak efektif di dalam ekosistem sekolah, dan kedisiplinan yang kurangditerapkan secara konsisten oleh sekolah. Program pelatihan yang diberikan bertujuan untuk meningkatkankompetensi guru dalam mengajar di sekolah inklusi, dengan tema “Pengenalan Karakteristik, Cara Berkomunikasi,dan Program Pembelajaran untuk Siswa Berkebutuhan Khusus”. Adapun pelaksanaan pelatihan ini terdiri dari tigasesi utama yaitu Sesi I membahas mengenai karakteristik PDBK di sekolah Inklusi, Sesi II membahas mengenaistrategi Komunikasi yang efektif antara Guru dengan Ekosistem Sekolah, dan Sesi III membahas mengenai carapenyusunan Program Pembelajaran Individual (PPI). Evaluasi terhadap pelatihan ditinjau dari dua aspek, yaituevaluasi kegiatan pelatihan dan evaluasi pencapaian tujuan. Dalam evaluasi pencapaian tujuan, tim fasilitatormelihat pencapaian tujuan setiap sesi berdasarkan tanggapan peserta saat berdiskusi, dan hasil dari pre-test sertapost-test. Hasilnya beberapa peserta mengalami peningkatan rata-rata skor pada post test dalam setiap sesi,walaupun hasilnya belum signifikan.